Field guide to the birds of the United States and Canada West - Floyd, Ted, 1968- (National Geographic, 2025)
An entirely updated edition of the classic bestselling regional bird field guide from National Geographic, covering the western U.S. and Canada, including Hawaii. Birdwatchers from the Rockies west will find nearly 1,000 species in this user-friendly guide, with all new text, updated art, and data-driven maps